Behind the Scenes of Inuit Curriculum Development in Nunavut, 2000–2013 - McGregor, Heather; McGregor, Catherine (Études Inuit Studies, 2016)
In this article we examine the provision of curriculum in Nunavut between 2000 and 2013. During this time the Government of Nunavut established a mandate to ensure all curriculum from Kindergarten through Grade 12 was founded on Inuit Qaujimajatuqangit (IQ) and supported bilingualism. We describe how the Curriculum and School Services Division of the Department of Education undertook to fulfil this responsibility through unique, made-in-Nunavut curriculum development processes and products. We conclude by outlining the opportunities and challenges evident in the work of creating curriculum, teaching resources, and learning materials that centre Inuit knowledges, languages, and contexts.